MSME Digitalization Using Point of Sale Calculator to Improve Efficiency and Productivity - Rony, Muhammad Ainur; Anggraeni, Motika Dian (LPPM Institut Teknologi Telkom Purwokerto, 2024)
Digitalization of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is crucial to increase competitiveness in the era of globalization. Due to cost considerations, many MSMEs continue to rely on conventional methods to manage their businesses, leading to inefficiencies in transaction handling and sales data analysis. This traditional approach often results in errors, reporting delays, and suboptimal decision-making, which can hinder growth and productivity. This study focuses on the implementation of a free cloud-based Point of Sale (POS) calculator application as a digital solution to address these challenges. The POS application streamlines the transaction process and generates real-time sales reports, ultimately improving operational efficiency and strategic decision-making. The development method used in this study is the System Development Life Cycle method. The POS application development process includes comprehensive Requirements Analysis, System and Software Design, Implementation, Testing, and Maintenance. User feedback was collected through structured interviews and surveys to evaluate the application's ease of use and its benefits in improving MSME operations. The findings showed significant improvements in operational efficiency, as the POS application speeds up transaction processing and provides timely, data-driven insights for decision-making.